The dynamics of the production in Romanian soya culture in 2010-2016 - Alexandra-Marina Brǎtulescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Soy is one of the most important crops for human, animal and plant feed. The content of soybeans is rich in protein and fat, which gives this crop a very high nutritional value. In this paper we will analyze the surfaces, outputs, prices and value of Romanian imports and exports, soybean culture, thus creating an overview of the study period, 2010-2016. This analysis highlights the evolution or involution of soybean production, using the method of comparative, quantitative and qualitative data analysis to determine their evolution.
Keywords: Q13; J11; 330; dynamic; soy; evolution; quantitative and qualitative